2005
DOI: 10.1021/ma050629s
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Effects of Aluminum Cocatalyst and Comonomer in Ethylene Copolymerizations Catalyzed by (Arylimido)(aryloxo)vanadium Complexes:  Efficient Synthesis of High Molecular Weight Ethylene/Norbornene Copolymer

Abstract: Copolymerizations of ethylene with norbornene (NBE), cyclopentene (CPE) and 1-hexene by (arylimido)(aryloxo)vanadium(V) complexes of the type VCl 2(N-2,6-Me2C6H3)(OAr) [Ar ) 2,6-Me2C6H3 (1), 2,6-i Pr2C6H3 (2), 2,6-Ph2C6H3 (3)] with cocatalyst [methylaluminoxane (MAO) or Et2AlCl] catalyst systems have been explored. These complexes exhibited remarkable catalytic activities for ethylene polymerization in the presence of Et 2AlCl cocatalyst; in particular, the resultant polyethylene prepared by 1 possessed narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
81
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 31 publications
5
81
0
Order By: Relevance
“…Heterogeneous Ziegler-Natta catalysts usually give copolymers with both broad comonomer distribution and wide molecular weight distribution, while homogeneous metallocene catalysts produce much more uniform copolymers [2,3]. Recently copolymerization in the presence of postmetallocene catalysts also became an interesting and important field of research [4][5][6][7][8][9][10][11]. Very efficient copolymerization postmetallocene catalysts are titanium complexes of the general formula [N-(3,5-di-tert-butylsalicylidene)-2-alkylsulfanylanilinato]Ti(IV)Cl 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous Ziegler-Natta catalysts usually give copolymers with both broad comonomer distribution and wide molecular weight distribution, while homogeneous metallocene catalysts produce much more uniform copolymers [2,3]. Recently copolymerization in the presence of postmetallocene catalysts also became an interesting and important field of research [4][5][6][7][8][9][10][11]. Very efficient copolymerization postmetallocene catalysts are titanium complexes of the general formula [N-(3,5-di-tert-butylsalicylidene)-2-alkylsulfanylanilinato]Ti(IV)Cl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, much interest was attracted by postmetallocene complexes which had vanadium as the central metal, both for homoand copolymerization of olefins [5][6][7][15][16][17][18][19][20][21]. Nomura and Wang [7] used (arylimino)(aryloxo)vanadium(V) complexes in ethylene/1-hexene copolymerization. However, poor 1-hexene incorporation was observed (0.8 mol%).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that (arylimido)vanadium(V) complexes, containing anionic donor ligands (L), V(N-2,6-Me 2 C 6 H 3 )Cl 2 (L) (L = aryloxo, ketimide, phenoxyimine etc. ), exhibited remarkable catalytic activities for ethylene polymerization in the presence of Al cocatalysts [3][4][5][6][7][8][9][10]. The activity by the aryloxo analogue was strongly affected by the Al cocatalyst; the activities in the presence of halogenated Al alkyls ( i Bu 2 AlCl, EtAlCl 2 , Me 2 AlCl, Et 2 AlCl) were higher than those in the presence of methylaluminoxane (MAO) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…), exhibited remarkable catalytic activities for ethylene polymerization in the presence of Al cocatalysts [3][4][5][6][7][8][9][10]. The activity by the aryloxo analogue was strongly affected by the Al cocatalyst; the activities in the presence of halogenated Al alkyls ( i Bu 2 AlCl, EtAlCl 2 , Me 2 AlCl, Et 2 AlCl) were higher than those in the presence of methylaluminoxane (MAO) [7,8]. Both the activity, and the norbornene incorporation, in the ethylene/norbornene copolymerization were also affected by the Al cocatalyst employed [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation